MOTIVASI ORANG TUA MENYEKOLAHKAN ANAK KE SEKOLAH ISLAM DAN IMPLIKASINYA TERHADAP KETENANGAN DI MI AL-CHAERIYAH - Rodiana Septiani; Abdul Ghofur (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2022)
Education is a vehicle for creating an easy generation that is very important for the future. Parents are responsible for their children’s education. Parents must provide encouragement and motivate children to continue their education to the next level, especially to choose a school with consideration and care, so that children get quality education so that parents do not regret it in the future. In this study is a qualitative research that uses data collection techniques through observation, interviews to parents of students and documentation that aims to obtain information related to the mativation of parents who send their children to Islamic schools. Based on the results of research at MI Al Chaeriyah. One of the motivations of parents to send their children to Islamic schools is so that their children understand the norms of Islamic teachings that are in accordance with Islamic law and can be applied in everyday life. Then the constrains for parents to send their children to Islamic schools is the economic fator, because Islamic schools have a lot of costs. Such as tuition fees, cash, exams, committees, and others. So parents who want to send their children to Islamic schools must have special savings for school needs. And the implication is that many of the students have the development of attitudes. Starting from better morals, speaking politely honestly, knowing the teachings and laws applied in Islam.